DINAMIKA PELABUAHAN MUARO PADANG 1945-1996 - EKSI, YATNI - (Pendidikan Sejarah, 2014)
Tis thesis is about " Dinamic of Muaro Padang Harbour form 1945 to 1996 " that has firm interlated to trade and foyage beach interurban and also intersland in Pesisir Barat West Sumatera in Revolution Era, Orde Baru, And Orde Lama in 1945-1996. The formulation of this research as follow: How the situation and condition Muaro Padang Harbour before freedom era and how sistem manage muaro padang harbour after freedomÂ  era and also development activity Muaro Padang Harbour in transp[ortation area between beach interurban and intersland in west pesisir barat Sumatera island untill 1996. This research uses history maritim and this research uses history method , ramely: (1) heuristic is a stage for collecting sources history data through dokumenter, literature, and interview .(2) Criticism (internal or eksternal criticism) is a proces for testing data legality based on deepest analysis.(3) Interpretation is an activity for interpreting data.(4) Historiography is a process of writing the thesis . The conclusion is the existence Muaro Padang Harbour have down activities bacause of ecologyÂ  factor of the harbour and also for increasing the highway construction and development of using land transportation. The tools and infrastructure comlete yet give influence to decrease Muaro Padang Harbour. Beside that harbour management is afactor too to make down activities in the harbour.